Ultrasound-assisted depolymerization of carrageenan from Kappaphycus alvarezii hydrolized by a marine fungus. Issue 1 (1st January 2023) - Tarman, K; Zuhair, M W; Uju,; Pari, R F
Abstract: Kappaphycus alvarezii is a species of red seaweed that produces kappa-carrageenan. Carrageenan is a polysaccharide containing D-galactose and 3, 6-anhydrogalactose units which linked by α-1, 3 and β-1, 4 glycosidic bonds. The study aimed to determine the optimal ultrasonication time in the carrageenan depolymerization process. In this study the hydrolysis process of K. alvarezii to obtain the carrageenan was carried out biologically using a marine fungus RS6A. Viscosity of the carrageenan was measured using Brookfield viscometer, which was then used to calculate the molecular weight by Mark-Houwink equation. The carrageenan's viscosity and molecular weight values varied between 3.73-6.13 cP and 35.58-52.15 kDa, and had an inverse correlation with the ultrasonication time. These results indicated that ultrasonication was effective in reducing molecular weight in the depolymerization process. The selected treatment was obtained by ultrasonication for 30 minutes with conformity to standards of carrageenan according to SNI 8391: 2017 and FAO (2014).